Elicitores abióticos no estresse oxidativo e na expressão de gene da rota de betacianina em Alternanthera philoxeroides (Mart.) Griseb. - Ribeiro, Márcia Vaz (2011)
The medicinal Alternanthera (Amaranthaceae) species, such as A. philoxeroides, present a great variety of bioactive compounds, among which are the betacyanins, nitrogen pigments that belong to the betalains class. These compounds are widely used as additives for food and drugs, due to their antioxidant action and lack of toxicity, which have already been proven. Techniques have been developed in order to improve productivity and performance of this pigment, one of those is the use of in vitro elicitors or in vivo stressing agents. Both have an important role in the transduction process of signals that regulate the defense genes in plants, acting as stimulators of production or degradation of several primary and secondary metabolites. This work aimed to assess, in A. philoxeroides plants, the growth and production characteristics of betacyanin in in vitro plants; the levels of photosynthetic pigments, betacyanins, lipid peroxidation and antioxidant enzymes activity in in vivo plants under salt stress, and also to quantify the level of betacyanin and the 5GT-DBs gene expression in the biosynthetic route of this compound in in vitro plants submitted to elicitation by NaCl and by tyrosine. For this, three trials were conducted. In the first one, A. philoxeroides explants were inoculated in MS medium with increasing NaCl concentrations (0, 50, 100, 150, 200 and 250 mM) for 35 days. In the second one, plants from in vitro cultures were acclimatized in greenhouses and irrigated with a sodium chloride solution (0, 200 and 400 mM) for 30 days. The third trial had two essays, one composed of in vitro A. philoxeroides plants in a liquid MS medium in vermiculite substrate for 35 days. After this period, a NaCl solution (400 mM) was added to the medium and the shoots were collected after 0, 12, 24, 36 and 48 hours of exposure. In the second one, nodal segments were inoculated in MS medium with and without tyrosine (0 e 75 µM), and its aerial parts were collected after 35 days. In the growth analysis, reduction of the averages was observed for the following variables: height, number of shoots, number of sprouts and root number and length; for the plants that have grown in the sodium chloride medium. The highest concentrations of betacyanins were found in the stalks of plants from MS medium, with 50 mM of NaCl. After 30 days of in vivo cultivation, the levels of chlorophyll a, chlorophyll b and carotenoids decreased as the salt concentration increased, while the reason of chlorophyll a/b in plants submitted to a higher salt concentration presented a difference in comparison to the control. Higher levels of betacyanin were observed on stalks, when compared to the leaves, in the highest salt concentrations. On the leaves, there was a significant increase of lipid peroxidation and superoxide dismutase activity. On the roots, there was an increase of enzymes catalase and ascorbate peroxidase. Regarding the analysis of differential expression (qRT-PCR), it was possible to observe that from 12 to 24 hours of salt stress, the 5-GT gene expression firstly increased, then there was a decrease in 36 hours and a new increase in 48 hours. The 5-GT gene also showed increased expression as a response to tyrosine. It was possible to conclude that A. philoxeroides elicited in vitro with sodium chloride present a decrease of the assessed morphological parameters, but in low concentrations betacyanin synthesis is stimulated. Salt stress causes greater degradation in the photosynthetic pigments, increment of betacyanin synthesis in stalks and damage to the cell membranes of the leaves. The increase of antioxidant enzymes activity stimulated the protective system against oxidative stress on in vivo A. philoxeroides plants. It is suggested that in this species, the enzyme bethanidine 5-Oglucosyltransferase reaches its highest expression in 48 hours of exposure to salt elicitation and also when grown in a medium containing tyrosine.